2020
DOI: 10.1007/s00500-020-05387-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: A topic-based hierarchical publish/subscribe messaging middleware for COVID-19 detection in X-ray image and its metadata

Abstract: Putting real-time medical data processing applications into practice comes with some challenges such as scalability and performance. Processing medical images from different collaborators is an example of such applications, in which chest X-ray data are processed to extract knowledge. It is not easy to process data and get the required information in real time using central processing techniques when data get very large in size. In this paper, real-time data are filtered and forwarded to the right processing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Numerous recent studies have also shown the superior role of superficial and deep learning-based intelligence in the diagnosis of COVID-19 patients using X-rays and CT scans with higher accuracy than the standard diagnostic approach [ 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous recent studies have also shown the superior role of superficial and deep learning-based intelligence in the diagnosis of COVID-19 patients using X-rays and CT scans with higher accuracy than the standard diagnostic approach [ 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a method based on chest X-ray imaging has become almost the most useful method to detect COVID19 positive cases [19]. However, this method suffers from the long-time needed by the radiologists to read and interpret X-ray images [20]. Besides, due to the increasing prevalence of the COVID19 virus, the number of patients, who need an X-ray image interpretation, is much higher than the number of radiologists leading to the radiologists overloaded, long-time diagnosis process, and a critical risk of other people's infection.…”
Section: Introductionmentioning
confidence: 99%
“…Eken [14], developed a topic-based publishsubscribe messaging scheme for supporting the detection of COVID-19 in X-ray image. The study adopted the use of a topic-based publishsubscribe model for the transfer of information between communication nodes over a distributed scalable network of collaborative computational nodes.…”
Section: Related Workmentioning
confidence: 99%